Principal Promotion Strategy in Increasing the Number of New Students - Susetiyo, Ari; Nugraha, Muhammad Zainuddin Ikhsan (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
The principal plays a very crucial role in increasing the number of students at Madrasah Ibtida'iyah Miftahul Muna, because the success of an educational institution is often determined by effective leadership and marketing strategies. The purpose of this study was to understand the strategies implemented by the principal in increasing the number of students, as well as the implementation and results of these strategies. The method used was a qualitative approach, with data collection through interviews, observations, and documentation. Data analysis was carried out using data collection techniques, data condensation, data presentation, and drawing conclusions. To ensure the validity of the data, increased persistence and triangulation were used. The results of the study showed that the principal's strategy to increase new student admissions at MI Miftahul Muna Prambon involved a promotion mix. The implementation of this strategy included activities such as advertising, personal selling, sales promotion, public relations, and direct marketing. The programs implemented were proven to be able to attract the attention of prospective new students, indicating the effectiveness of the strategies implemented. The contribution of this study is to provide new insights into the integration of various marketing strategies in the context of educational institutions, as well as offering practical examples that can be adopted by other educational institutions to increase student admissions.